KAJIAN KUAT LEKAT TULANGAN PADA FLOW!NG CONCRETE DITINJAU DAR! TINGGI JATUH PENGECORAN - Nuriyadin Eko Raharjo Aspin (Universitas Negeri Yogyakarta, 2007)
AbstractPumping method that widely used in the stage of concreting forhigh rise building construction, will lead the fresh concrete into the risksof bleeding and segregation that can caused inadequate concrete qualitydue to the presence of more pores volume in hardened concrete.Interfacial transition zone between plain concrete and reinforcing bar is amain factor that dominantly determine the mechanical strength ofreinforced concrete members as a composite material. Fresh concretecharacteristics, casting method, and free fall height will mainly affect thebond strength of a reinforced concrete structural member. This researchaimed to investigate the effects of free fall height in the concrete castingon the bond strength of concrete reinforcement.Concrete material that used in this research mixed using OrdinaryPortland Cement with 0.45 of water-cement ratio, 1% of polycarboxylatebased high range water reducer by weight of Portland cement, and a 16mm of deformed steel reinforcing bar with 403.06 IP̃a of yield strength.The experiment was done on the free fall heights of 0 em, 30 em, 75 em,100 em, 200 cm, and 300 em. Investigation of concrete compressivestrength was done using 18 15x15x15 cm3 standard cubes, and bondstrength using 18 standard samples of reinforcing bar casted in15x15x15 cm3 concrete cubes.The experimental test indicates that free fall height significantlyaffects bond strength of steel reinforcement in a reinforced concretestructural member. The optimum bond strength was achieved on 30 cmof free faU height, and the failure of the samples meet with rull-outmechanism. This result can be explained due to the presence ofgravitational force that lead the fresh concrete into an initial compactingprocess by its own weight, when bleeding and segregation do not existit: the casted fresh concrete.Keywords: strength of steel reinforcement, floowing concrete,superplasticizer